2006
DOI: 10.1002/jcc.20494
|View full text |Cite
|
Sign up to set email alerts
|

Bond order and valence indices: A personal account

Abstract: Abstract:The paper accounts for the author's activity in developing bond order and valence indices since the early 80s.These indices represent an important conceptual link between the physical description of molecules as systems of electrons and nuclei and the chemical picture of molecules consisting of atoms kept together by bonds. They are also useful for a systematization and interpretation of the results obtained in the quantum chemical calculations, by permitting to extract from the wave function differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
401
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 473 publications
(421 citation statements)
references
References 57 publications
(106 reference statements)
10
401
0
3
Order By: Relevance
“…Further evidence in support of the 2c-3e bond is collected in Table I, with details of the calculations given in the supplementary material. 24 Specifically, it is shown that the bond lengths (R e ) in the halogen complexes are much shorter than the corresponding van der Waals distances (R vdW ), 40 and their fuzzy bond orders defined by Mayer 41 are also much larger than other complexes. Perhaps the most convincing evidence is the integrated half-spin densities, which exhibits substantial delocalization between the halogen and oxygen moieties in the pertinent complexes.…”
mentioning
confidence: 97%
“…Further evidence in support of the 2c-3e bond is collected in Table I, with details of the calculations given in the supplementary material. 24 Specifically, it is shown that the bond lengths (R e ) in the halogen complexes are much shorter than the corresponding van der Waals distances (R vdW ), 40 and their fuzzy bond orders defined by Mayer 41 are also much larger than other complexes. Perhaps the most convincing evidence is the integrated half-spin densities, which exhibits substantial delocalization between the halogen and oxygen moieties in the pertinent complexes.…”
mentioning
confidence: 97%
“…(36), owing to the fact that for the expectation values of the "mixed" pairs of creation and annihilation operators one has (in the single determinant case) [1,6] …”
Section: The "Chemical" Hamiltonianmentioning
confidence: 99%
“…23 It was shown by Borisova and Semenov 25 for the Wiberg index 26 of the complete neglect of differential overlap ͑CNDO͒ theory and by one of us for the ab initio 27 that the bond order index calculated in the Hilbert-space framework may be considered as the effective number of electron pairs participating in the bonding between the atoms considered. 28 This should be applicable mutatis mutandis in the fuzzy atoms frame as well.…”
Section: ͑13͒mentioning
confidence: 99%